2023
DOI: 10.1111/jch.14758
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypertension with the triglyceride–glucose index and its associated indices in the Chinese population: A 6‐year prospective cohort study

Changqiang Yang,
Yue Song,
Xinquan Wang
et al.

Abstract: The authors aim to assess the correlation between hypertension and the triglyceride‐glucose (TyG) index and its associated indices, and to compare their abilities to identify hypertension. Four thousand eight hundred and sixty‐six non‐hypertensive participants were enrolled from the China National Health Survey in 2009. The data on new‐onset hypertension were gathered in both 2011 and 2015. The TyG index and its associated indices were derived from the fasting triglyceride, blood glucose levels, and anthropome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…The roots ofZanthoxylum nitidum (ZN) are a type of tea in southern China, which can be used to relieve neuralgia and headache . In recent years, with the aging in the Chinese population, many diseases such as hypertension, hyperglycemia, hyperlipidemia, and Alzheimer’s disease are common in the elderly. , Zanthoxyli radix is becoming increasingly popular among the elderly population. This tea contains a rich and diverse range of chemical components, mainly including alkaloids, flavonoids, coumarins, and lignans with various biological activities such as anti-inflammatory and antioxidant effects. Zheng et al found that flavonoids in ZN possessed the antioxidant capacity by DPPH method .…”
Section: Introductionmentioning
confidence: 99%
“…The roots ofZanthoxylum nitidum (ZN) are a type of tea in southern China, which can be used to relieve neuralgia and headache . In recent years, with the aging in the Chinese population, many diseases such as hypertension, hyperglycemia, hyperlipidemia, and Alzheimer’s disease are common in the elderly. , Zanthoxyli radix is becoming increasingly popular among the elderly population. This tea contains a rich and diverse range of chemical components, mainly including alkaloids, flavonoids, coumarins, and lignans with various biological activities such as anti-inflammatory and antioxidant effects. Zheng et al found that flavonoids in ZN possessed the antioxidant capacity by DPPH method .…”
Section: Introductionmentioning
confidence: 99%